(untitled) (Research, Society and Development, 2022)
Contemporary society is constantly changing social representations, customs and the conception of education as formation, nourished by globalization and technological advances driven by neoliberalism, which seeks to expand the market of goods and services reaffirming the capitalist logic. In this universe, the teacher is a fundamental piece, but the need for a teacher professional training that enables theories and practices directed to an education facilitating the social, cultural and professional emancipation of the student is still seen. The aim of this article is to address the challenges for teacher training and professional development that enables quality and humanized education in the face of neoliberalism, based on a bibliographic review, of a qualitative-descriptive nature. Studies show that, in order to have an education with the humanized, critical and emancipatory formation of future generations, in a bias of social, cultural, intellectual and professional growth, it takes the mastery of the teacher to lead the process of construction of this new world that is to come, in addition to the articulation of others involved in the educational process to promote an integral and integral education.